Review of Artificial Intelligence In Accounting: Trends, Implementation and Implications - Mediaty, Mediaty; Indrijawati, Aini; Pratama Kohar, Yansen; Sutriani, Sutriani; Salsabila, Tsarwah (Journal of Accounting and Finance Management, 2024)
In the context of the industrial revolution 4.0, the use of advanced technologies such as artificial intelligence (AI), data analytics, and automation has fundamentally changed accounting practices. This article aims to explore and analyze recent developments in accounting practices through a systematic review of existing literature. The focus of the study is on how information technology and data analytics affect accounting practices and managerial decision-making. The methodology used is a systematic literature review, which involves collecting and analyzing relevant studies from various academic sources and leading journals with strict inclusion and exclusion criteria. This article shows a significant increase in the adoption of information technology and data analytics among accounting professionals, as well as challenges in its implementation, such as the need for training and adaptation to change. The conclusion of this article recommends the development of a comprehensive training program to help accounting professionals adapt to technological changes. This article is expected to make a significant contribution to the understanding of current dynamics in the accounting field and direct further research in the future.